2018
DOI: 10.1016/j.plefa.2018.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Safety and tolerability of prescription omega-3 fatty acids: A systematic review and meta-analysis of randomized controlled trials

Abstract: RxOME3FAs are generally safe and well tolerated but not free of adverse effects. Post-marketing surveillance and observational studies are still necessary to identify long-term adverse effects and to confirm the safety and tolerability profiles of RxOME3FAs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(48 citation statements)
references
References 62 publications
0
43
0
5
Order By: Relevance
“…There were no SAEs and no group differences in AEs, with the exception of muscle cramps, which were reported more frequently in the fish oil group. Gastrointestinal AEs, which are commonly reported during fish oil supplementation (Chang et al 2018), were reported at a similar frequency in both treatment groups. Consistent with prior evidence that chronic high-dose fish oil (Harris 2007) or elevated n-3 PUFA blood levels (Salisbury et al 2012) are not associated with clinically significant increases in bleeding time in adult patients with cardiovascular diseases, we did not observe significant group differences in bleeding-related AEs or baseline-endpoint changes in laboratory measures of hemostasis.…”
mentioning
confidence: 54%
“…There were no SAEs and no group differences in AEs, with the exception of muscle cramps, which were reported more frequently in the fish oil group. Gastrointestinal AEs, which are commonly reported during fish oil supplementation (Chang et al 2018), were reported at a similar frequency in both treatment groups. Consistent with prior evidence that chronic high-dose fish oil (Harris 2007) or elevated n-3 PUFA blood levels (Salisbury et al 2012) are not associated with clinically significant increases in bleeding time in adult patients with cardiovascular diseases, we did not observe significant group differences in bleeding-related AEs or baseline-endpoint changes in laboratory measures of hemostasis.…”
mentioning
confidence: 54%
“…The Matsuyama paper studied a nutritional intervention for a chronic disease: it purported to show that a diet rich in omega-3 polyunsaturated fatty acids reduced inflammation and improved exercise capacity in persons with chronic obstructive pulmonary disease (COPD). Omega-3 polyunsaturated fatty acids are of particular interest as an adjunct to conventional pharmacotherapies in people with inflammatory diseases such as hypertriglyceridemia and rheumatoid arthritis, due to the cost-effectiveness and favorable safety profile (Calder and Zurier 2001;Chang et al 2018;Samuel et al 2011). The design used in the Matsuyama study is the strongest established method for showing treatment efficacy: a randomized controlled trial (RCT).…”
Section: Case Studymentioning
confidence: 99%
“…Indeed, in a recent systemic review and meta-analysis dedicated to the safety and tolerability of prescription of omega-3 fatty acids, fishy taste and belching were significantly more frequent in treated subjects than in controls. 44 What Should be the Next Step?…”
Section: Pufas Supplementation For Adhdmentioning
confidence: 99%